Human resource development experience of some developed countries and lessons drawn for Vietnam today (Revista de Investigaciones Universidad del Quindío, 2022)
As the Fourth Industrial Revolution is strongly growing, human resources, especially high-quality ones, play a decisive role in the socio-economic development of each country. Therefore, priority is given by many countries to building and developing human resources, because, in the current context, human resources fully equipped with skills and knowledge will contribute to the development of individuals, organizations and countries. From the strong economic development of the US, Japan and Western countries in the mid-20th century to the title of “Asian Tigers” given to four economies in East Asia and the rapid growth of ASEAN countries, all thanks to policies of human resource development. However, in different countries, the development of human resources is implemented in different directions depending on the economic, cultural and social conditions of each country. In Vietnam, after nearly 35 years of renovation, the country has earned great achievements in human resource development, most clearly reflected in the productivity improvement of the whole society, which speeds up the growth rate and enhances economic competitiveness and national potential. Also, it is necessary to admit that, compared to the resources invested and efforts spent, as well as the conditions and opportunities offered, the achievements mentioned above are still not commensurate with the country’s potential. Therefore, this article aims to discuss the human resource development strategies of some countries in the world, thereby drawing lessons for Vietnam.
Keywords: Human resource development; human resource; human resource development in Vietnam